Student Assessment of the Use of Kahoot in the Learning Process of Science and Mathematics - Marta Curto Prieto; Lara Orcos Palma; Pedro Jesús Blázquez Tobías; Francisco Javier Molina León (MDPI AG, 2019)
One of the main objectives in education is to increase the motivation of the students to achieve meaningful learning. The use of technologies in classrooms which students are familiarized with such as the smartphone or the tablet, is a way to achieve this goal. On the other hand, it has been proven that the inclusion of scenarios supported by games and competition enhance the active participation of students. Therefore, in this work we present the results of a study based on of the application Kahoot with students of secondary education, in the subjects of mathematics, biology & geology and physics & chemistry, during the academic year 2017/2018. This tool allows students to answer to on-line questionnaires created by the teacher, through mobile devices, and check their results in a few seconds as well as those of their classmates. The results obtained on the assessment of the tool by students, in terms of the benefits in the learning process, have been very positive and help us to examine the potential of the use of on-line questionnaires in the classrooms.